PENGEMBANGAN MODUL IPA BERBASIS ETNOSAINS PEMBUATAN IKAN ASAP PADA MATERI ZAT DAN PERUBAHANNYA - Syahputri, Cindy Eka; Hadi, Wiwin Puspita; Wulandari, Ana Yuniasti Retno; Yamin, Yamin; Hartiningsih, Try (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2025)
This study aims to determine the feasibility of the Ethnoscience-Based Science Module for Making Smoked Fish, the readability of the Ethnoscience-Based Science Module for Making Smoked Fish, and students' responses to the Ethnoscience-Based Science Module for Making Smoked Fish. The development model used is the ADDIE development model. The subjects of this study were grade VII students of SMP Negeri 15 Surabaya. The results of this study indicate that 1) the developed Science Module was declared